Progress in economics research. - Tavidze, Albert (Nova Science Publishers, 2018)
This compilation opens with an address of the way in which economic growth in Malaysia largely relies on external market conditions, despite the fact that Malaysia successfully shifted from an agriculturally-based economy to one that is manufacturing-based. Thus, the authors present an in-depth discussion of economic growth and human capital development plans and their impacts on the labor market in Malaysia. Next, the authors offer an original justification for a new generation of regional economic policy for contemporary Ukraine through proper gradual representation of its basic elements. The logic and reshaping principles of forming an internal circuit of regional economic policy modernization are presented, along with ways to reconcile the interests of the national and regional levels when revising a regional policy and more. The French economy from 2010 to 2017 is reviewed, particularly covering the areas of industry, agriculture, the services sector and international trade. Also covered are employment trends and the labour market reforms over this period. Following this, the authors examine the impact of new technologies on office employment, particularly on clerical jobs, in Mexico. Drawing on recent research on the evolution of job offers published by a leading Mexican newspaper, the authors are able to conclude that office jobs are no longer defined by traditional skills but by multitasking ability. This collection goes on to discuss how the advancement of information technology, in conjunction with the popularity of mobile payment, has facilitated a drastic growth of e-commerce retail business around the globe in the past decade. In order to focus on core business processes such as product development and promotion, e-retailers commonly outsource the logistics and distribution aspects of e-commerce business to third-party logistics service providers. The objective of the following chapter is to determine the contribution of inequality of opportunities to the distribution of accessibility to basic education between 2001 and 2007 in Cameroon. The results lead the authors to recommend a reinforcement of policies such as the abolition of tuition fees, the organization of awareness campaigns for the under-educated and the distribution of scholarships to girls and vulnerable children. The authors suggest that a closer look at recent overlapping generations models (with renewable resources that are costly to harvest) lends support to the view of classical economists who took the existence of the stationary state of a competitive market economy for granted.